1996
DOI: 10.1177/000331979604700904
|View full text |Cite
|
Sign up to set email alerts
|

Geometry of the Carotid Arteries and Tilt-up Hypotension in Subjects with Essential Arterial Hypertension

Abstract: Dysfunction of the baroreceptor structures located in the carotid bulb is considered responsible for hypotensive responses to orthostatic posture in hypertensive subjects. Because of a recurrent vascular impairment in essential hypertensives, the authors hypothesized that in these cases the baroreceptive dysfunction could be related to some peculiar vascular disarrangement of the carotid arteries, at the level of the bulb. To test this, they compared two groups of mild essential hypertensives, divided into gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2003
2003
2003
2003

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Similarly, Lage et al [16]found a significant correlation between the baroreflex function and compliance of the common carotid artery. However, reduced arterial compliance is not solely responsible for baroreflex dysfunction [17]. Ciccone et al [17]investigated the anatomy of the carotid region and hypothesized that in subjects with essential arterial hypertension, the baroreceptive dysfunction could be related to some peculiar vascular derangement of the carotid arteries at the level of the bulb.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Lage et al [16]found a significant correlation between the baroreflex function and compliance of the common carotid artery. However, reduced arterial compliance is not solely responsible for baroreflex dysfunction [17]. Ciccone et al [17]investigated the anatomy of the carotid region and hypothesized that in subjects with essential arterial hypertension, the baroreceptive dysfunction could be related to some peculiar vascular derangement of the carotid arteries at the level of the bulb.…”
Section: Discussionmentioning
confidence: 99%
“…Ciccone et al [17]investigated the anatomy of the carotid region and hypothesized that in subjects with essential arterial hypertension, the baroreceptive dysfunction could be related to some peculiar vascular derangement of the carotid arteries at the level of the bulb. They concluded that an impairment of the baroreceptor reflex in mild essential hypertension is more directly related to a derangement of the carotid artery structure, not arterial compliance [17]. …”
Section: Discussionmentioning
confidence: 99%